Interleukin 6 signaling regulates promyelocytic leukemia protein gene expression in human normal and cancer cells - Hubackova, Sona; Krejcikova, Katerina; Bártek, Jiří; Hodny, Zdenek (The Journal of biological chemistry, 2012)
Tumor suppressor PML is induced under viral and genotoxic stresses by interferons and JAK-STAT signaling. However, the mechanism responsible for its cell type-specific regulation under non-stimulated conditions is poorly understood. To analyze the variation of PML expression, we utilized three human cell types, BJ fibroblasts and HeLa and U2OS cell lines, each with a distinct PML expression pattern. Analysis of JAK-STAT signaling in the three cell lines revealed differences in levels of activated STAT3 but not STAT1 correlating with PML mRNA and protein levels. RNAi-mediated knockdown of STAT3 decreased PML expression; both STAT3 level/activity and PML expression relied on IL6 secreted into culture media. We mapped the IL6-responsive sequence to an ISRE(-595/-628) element of the PML promoter. The PI3K/Akt/NFκB branch of IL6 signaling showed also cell-type dependence, being highest in BJ, intermediate in HeLa, and lowest in U2OS cells and correlated with IL6 secretion. RNAi-mediated knockdown of NEMO (NF-κ-B essential modulator), a key component of NFκB activation, suppressed NFκB targets LMP2 and IRF1 together with STAT3 and PML. Combined knockdown of STAT3 and NEMO did not further promote PML suppression, and it can be bypassed by exogenous IL6, indicating the NF-κB pathway acts upstream of JAK-STAT3 through induction of IL6. Our results indicate that the cell type-specific activity of IL6 signaling pathways governs PML expression under unperturbed growth conditions. As IL6 is induced in response to various viral and genotoxic stresses, this cytokine may regulate autocrine/paracrine induction of PML under these pathophysiological states as part of tissue adaptation to local stress.
Keywords: signální transdukce; Signal Transduction; transkripční faktory STAT; Janus Kinases; Humans; HeLa buňky; sekvence nukleotidů; DNA primery; Transcription Factors; nádorové supresorové proteiny; akutní promyelocytární leukemie; Janus kinasy; Interleukin-6; jaderné proteiny; lidé; Tumor Suppressor Proteins; fluorescenční protilátková technika nepřímá; Base Sequence; HeLa Cells; interleukin-6; Nuclear Proteins; DNA Primers; Real-Time Polymerase Chain Reaction; Fluorescent Antibody Technique, Indirect; transkripční faktory; Leukemia, Promyelocytic, Acute; Chromatin Immunoprecipitation; chromatinová imunoprecipitace; kvantitativní polymerázová řetězová reakce; STAT Transcription Factors